Предмет: Алгебра,
автор: Dimchik20017
(6-x)+(12+x)-(3-2x)=15
Решение
Ответы
Автор ответа:
0
6-x+12+x-3+2x=15
2x=12
x=6
2x=12
x=6
Автор ответа:
0
просто не перенесли 12 ,забыли наверное) бывает
Автор ответа:
0
да,простите
Автор ответа:
0
(6-x)+(12+x)-(3-2x)=15 (раскроем скобки)
6-x+12+x-3+2x=15 (привелем подобные слангаемые)
15+2х=15
2х=0
х=0
Ответ : х=0
6-x+12+x-3+2x=15 (привелем подобные слангаемые)
15+2х=15
2х=0
х=0
Ответ : х=0
Похожие вопросы
Предмет: Алгебра,
автор: stasenkokarina1237
Предмет: Математика,
автор: aminotransferas
Предмет: Английский язык,
автор: ggghh5678
Предмет: Физика,
автор: 1998zxc